2012
DOI: 10.1161/circulationaha.112.103176
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylation Inhibition in Pulmonary Hypertension

Abstract: Background Epigenetic programming, dynamically regulated by histone acetylation, is a key mechanism regulating cell proliferation and survival. Little is known about the contribution of histone deacetylase (HDAC) activity to the development of pulmonary arterial hypertension (PAH), a condition characterised by profound structural remodelling of pulmonary arteries and arterioles. Methods and results HDAC1 and HDAC5 protein levels were elevated in lungs from human idiopathic PAH and in lungs and right ventricl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(119 citation statements)
references
References 47 publications
5
108
0
Order By: Relevance
“…Together with Zhao and colleagues, 80,81 we showed that VPA and the pan-HDAC inhibitor, SAHA, can reverse existing PH and RV hypertrophy in male SD rats exposed to normobaric hypoxia. Rats were housed under hypoxic conditions for 2 weeks before HDAC inhibitor treatment, via drinking water, for 2 additional weeks; immunoblotting confirmed that HDAC inhibitor treatment increased histone acetylation in the lungs.…”
Section: Hdac Inhibitors In Models Of Ph and Rv Hypertrophymentioning
confidence: 57%
See 2 more Smart Citations
“…Together with Zhao and colleagues, 80,81 we showed that VPA and the pan-HDAC inhibitor, SAHA, can reverse existing PH and RV hypertrophy in male SD rats exposed to normobaric hypoxia. Rats were housed under hypoxic conditions for 2 weeks before HDAC inhibitor treatment, via drinking water, for 2 additional weeks; immunoblotting confirmed that HDAC inhibitor treatment increased histone acetylation in the lungs.…”
Section: Hdac Inhibitors In Models Of Ph and Rv Hypertrophymentioning
confidence: 57%
“…79 Consistent with this, in a separate study, both SAHA and VPA were shown to stimulate the p21 CDK in lungs of chronically hypoxic rats, and this was associated with reduced pulmonary arteriolar muscularization. 80 HDAC inhibitors also reduced expression of the antiapoptotic protein BCL-2 in these rats, which suggests that HDAC inhibition blocks pulmonary vascular remodeling by concomitantly suppressing cell proliferation and promoting cell death.…”
Section: Mechanisms Of Action Of Hdac Inhibitors In Phmentioning
confidence: 79%
See 1 more Smart Citation
“…Elevated levels of HDAC1 and HDAC5 have been observed in the PAH lungs, and treatments with HDACi such as SAHA and VPA reduce disease worsening in rat models of pulmonary hypertension [105]. In addition, MEF2 might have a protective role in PAH progression as the expression of MEF2 and its transcriptional targets are signiicantly decreased in pulmo-nary artery ECs from patients with PAH.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Zinc-binding motifs have been considered as potential PH drug-therapeutic targets with phosphodiesterase type 5 (PDE5) and histone deacetylases as examples [54,55]. Zinc is a structural component of a number of intracellular enzymes, transcription factors, other proteins and cofactors and is a putative drug target for PH.…”
Section: New Advances: Hypoxic Induction Of Zinc Transportersmentioning
confidence: 99%